TECHNOLOGICAL FACTORS AFFECTING THE STORAGE OF THE QUALITY OF SEMI-HARD CHEESES - Khakimov Zafar Tulyaganovich; Rahmatov Khudoyor Boboniyozovich; Abdumannonov Axror Abdurasul o’g’li; Pardaboyev O’rolbek Saydvaliyevich; Muzaffarov Sarvar Sanjar o’g’li; Murodov Dilshod Komiljon o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
The article shows that the formation of the organoleptic characteristics of cheeses occurs in the process of its maturation, i.e. aging under certain temperature and humidity conditions as a result of enzymatic processes that cause a change in all components of the cheese mass and the formation of a characteristic taste and texture. Cheese is stored at lower temperatures, but the enzymatic processes do not stop, but proceed more slowly. The factors influencing the preservation of consumer characteristics of cheeses during storage until the expiration date, such as the quality of the original milk, the nature of the origin of the milk-clotting enzyme preparation, are considered. A very important factor in preserving the consumer characteristics of cheese during storage is the compliance of its chemical composition with the recommended parameters. Of particular importance are the mass fraction of moisture, active acidity and mass fraction of salt. When forecasting for long-term storage of semi-hard cheese, in order to preserve its organoleptic characteristics until the end of the shelf life, it is necessary to reduce the mass fraction of moisture as much as possible. The combination of high humidity, low pH and high salt content is critical.